Narrating the field diary: challenges and limitations of the methodological track for migrations in pandemic times - Santos Souto de Andrade, Carolina (2022)
The arrival of the pandemic by covid-19 and the different health contingency measures had generated very different impacts and responses in the world. They accentuated inequalities, exposed the great privileged of global geopolitics and in the Latin American case exposed the fragility of public institutions in the face of the advance of advance of the disease. In the midst of this disastrous scenario, public science was barely advancing. Affecting several researchers from all areas of knowledge, as myself, we continue to try to think strategies and alternatives for research in pandemic times. Under different levels of risk, resources and possibilities that surely made us more precarious in these times, creative imagination and technological devices gained even more prominence in doing research. Undoubtedly the pandemic has been a historical event for these generation. The covid-19 has modified, interrupted and transformed doing research from the year 2020. It has impacted my Ph.D. research with the Venezuelan migrants. In this article I seek to reflect some of these transformations. Keywords: Precariousness, immigration, narrative, methodology.